Teknik Pemeriksaan Radiografi Thorax PA pada Kasus Tuberkulosis di Unit Radiologi Rumah Sakit Umum Daerah Dr. Djasamen Saragih Pematangsiantar - Harahap, Veryyon; Simamora, Khoirun Nisa; Winanda, Dita (3031-8572, 2023)
Tuberculosis (TB) is a chronic infectious disease caused by Mycobacterium tuberculosis, primarily affecting the lungs. Chest radiography remains the primary imaging modality for diagnosing pulmonary tuberculosis. This study aims to determine the radiological examination technique for pulmonary tuberculosis cases and evaluate whether the PA or AP projection alone is sufficiently effective for establishing TB diagnosis at Dr. Djasamen Saragih Regional General Hospital, Pematangsiantar. This is a qualitative descriptive study using secondary data collection methods through observation, physical examination, and documentation. The subject was a 48-year-old male patient with a diagnosis of recurrent pulmonary tuberculosis showing patchy opacities. Radiographic examination was performed using PA projection with the patient in an erect position, exposure factors of 125 kVp and 250 mAs, using a 35x35 cm cassette at 150-180 cm FFD. The results showed that PA projection effectively visualized tuberculous lesions in the upper lung fields, including the apices. Although AP Lordotic projection could provide better visualization of apical lesions free from clavicular superimposition, the PA projection alone was deemed sufficient for establishing TB diagnosis at this facility. Radiation protection was implemented through collimation and proper field size management, though patient shielding with lead apron was not utilized to avoid interfering with the diagnostic area. It is concluded that PA projection chest radiography can adequately diagnose pulmonary tuberculosis cases, although the addition of AP Lordotic projection would be beneficial for evaluating small apical lesions that may be obscured by clavicular superimposition.